The Effect of Joint Damage on a Coal Wall and the Influence of Joints on the Abutment Pressure on a Fully Mechanised Working Face with Large Mining Height - Weibin Guo (Hindawi Limited, 2021)
Coal wall spalling is regarded as a key technical problem influencing safe and efficient mining of large-mining-height working faces while the distribution of abutment pressure within the limit equilibrium zone (LEZ) influences coal wall spalling within a large-mining-height working face. This research attempted to explore the distribution characteristics of abutment pressure within the LEZ in a large-mining-height working face. For this purpose, the influences of the orientation of joints on mechanical characteristics of coal with joints and on the distribution of abutment pressure within the LEZ in the large-mining-height working face were analysed by theoretical analysis and numerical simulation. Research results show that the damage variable of coal with joints first rises, then decreases, and finally increases with increasing dip angle of the joints; as the azimuth of the joints increases, the damage variable first declines, then increases; the damage variable gradually declines with increasing joint spacing; an increase in the dip angle of joints corresponds to first reduction, then growth, and a final decrease of the abutment pressure at the same position in front of the coal walls; on certain conditions, the abutment pressure at the same position within the LEZ first rises, then declines as the azimuth of joints increases; with the growth of the joint spacing, the abutment pressure at the same position within the LEZ rises. The dip angle and azimuth of joints marginally affect the abutment pressure within the LEZ.